2017
DOI: 10.1371/journal.pone.0182137
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin rich extract of Brassica oleracea L. alleviates experimentally induced myocardial infarction

Abstract: Cardioprotective potential of anthocyanin rich red cabbage extract (ARCE) was assessed in H2O2 treated rat neonatal cardiomyoblasts (H9c2 cells) and isoproterenol (ISO) induced rodent model of myocardial infarction. H2O2 treated H9c2 cells recorded cytotoxicity (48–50%) and apoptosis (57.3%), the same were reduced in presence of ARCE (7–10% & 12.3% respectively). Rats pretreated with ARCE for 30 days followed by ISO treatment recorded favourable heart: body weight ratio as compared to ISO treated group. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
(46 reference statements)
3
19
0
Order By: Relevance
“…Apoptosis markedly shares in mediation of MI including cleaved caspase‐3, TNFα, and BAX/Bcl‐2 pathway. We found the same in ISO‐ induced MI group, and this is in line with Xu et al , Kumar et al , Jana et al , and Bin‐Jaliah et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Apoptosis markedly shares in mediation of MI including cleaved caspase‐3, TNFα, and BAX/Bcl‐2 pathway. We found the same in ISO‐ induced MI group, and this is in line with Xu et al , Kumar et al , Jana et al , and Bin‐Jaliah et al .…”
Section: Discussionsupporting
confidence: 92%
“…The B‐cell lymphoma‐2 (Bcl‐2) family is a potent regulator of the apoptotic pathways. This family of proteins includes both anti‐apoptotic and pro‐apoptotic proteins such as Bcl‐2 associated X protein (Bax) and Bcl‐2, respectively . Moreover, oxidative stress has a key role in mediating MI and antioxidants represent the first line of defense against it.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, anthocyanins from cabbage have strong antioxidant activity (22.0 mmol Fe(II)/g fw), which is approximately 10-fold higher than green cabbage (Yuan et al, 2009), suggesting for similar studies with purple cauliflower. Further, Jana et al (2017) reported total anthocyanin content in red cabbage extract was found to be 86.004 ± 3.103 mg/100 g and elucidated the mechanism of ARCE mediated prevention of experimentally induced myocardial damage in rodent model. These investigations suggests for further studies to understand the potential of purple color Brassica vegetables for good health.…”
Section: Discussionmentioning
confidence: 94%
“…Hydrogen peroxide (H 2 O 2 ) is a major component of ROS in the cells activated by various external stimuli that trigger internal deleterious responses. In cardiomyocytes, H 2 O 2 -induced oxidative stress can stimulate MAPK signaling pathways that are closely associated with cell death and cell survival (Nam, Hah, Nam, Kim, & Park, 2016), which is why reduction of intracellular ROS production is a major target in regulating ischemic injury in cardiomyocytes (Jana et al, 2017).…”
mentioning
confidence: 99%
“…Isaak et al observed that lingonberry anthocyanins could protect cardiac cells from loss of membrane permeability and chromatin condensation (Isaak, Petkau, Blewett, Karmin, & Siow, 2017). Also, anthocyanin rich extract of Brassica oleracea L. prevented the depletion of enzymatic antioxidants (SOD and Catalase;Jana et al, 2017).…”
mentioning
confidence: 99%